Comparative characteristics of COVID-19 vaccines used for mass immunisation - G. G. Onishchenko; T. E. Sizikova; V. N. Lebedev; S. V. Borisevich (Биопрепараты: Профилактика, диагностика, лечение, 2021)
The pandemic of the new coronavirus (COVID-19) disease that began in December 2019 in China is still having a huge impact on all spheres of human life. The herd immunity, which is the most effective tool for preventing the spread of the disease, is formed in two ways: the passive way (i.e., the formation of a population not susceptible to re-infection due to the natural spread of the disease) and the active way (mass immunisation). High rates of COVID-19 vaccination were achieved thanks to the development and mass production of new vaccines. The selection of the most promising vaccine platforms is one of the key aspects of successful mass immunisation. The aim of the study was to compare the characteristics of COVID-19 vaccines used for mass immunisation. The paper analyses the vaccine technology platforms, efficacy of different types of vaccines based on clinical trial results, safety of vaccines for different population groups, and potential for scaling up vaccine production in order to ensure the necessary vaccination coverage. The vaccines currently used for mass immunisation are: BNT162b2 (Pfizer/BioNTech), mRNA1273 (Moderna), Gam-COVID-Vac (N.F. Gamaleya National Research Center for Epidemiology and Microbiology), Ad26.COV2.S (Johnson & Johnson), ChAdOx1-S (AZD1222) (AstraZeneca), BBIBP-CorV (Sinopharm), CoronaVac (Sinovac Biotech), and NVX-CoV2373 (Novavax). The comparison of the main characteristics of the vaccines demonstrated that the most promising types of vaccines for COVID-19 specific prophylaxis are RNA vaccines and recombinant adenovirus vector-based vaccines.